Resolving Cultural Ambiguity in the Kurdish Language - Hasan, Dr. Farhad Tawfiq (Sulaimani Journal for Humanities, 2025)
This research, titled "Overcoming Lexical Gaps in the Kurdish Language," examines the phenomenon of lexical gaps, particularly the absence of specific terms or expressions within the Kurdish language to describe concepts or objects that exist in other languages. Lexical gaps emerge due to various factors, such as cultural, social, and environmental influences. While many reasons contribute to the existence of these gaps, it is a misconception to attribute them solely to external factors, such as a lack of scientific development in the Kurdish language. This view often reflects a limited understanding of both linguistics and Kurdish culture. The second part of the research delves into the extent of lexical gaps in Kurdish, identifying their specific causes, and offering practical solutions for addressing them. Additionally, the study outlines linguistic strategies and procedures that can be employed to resolve these gaps and enrich the Kurdish lexicon.
Keywords: Cultural calque; Causes of cultural calque; Lexical solutions; Syntactic solutions; Morphological processes; Syntactic processes